The effect of previous preterm birth on the risk of recurrent preterm birth in Iceland 1997-2018 - Ása Dóra Gylfadóttir 1991- (2023)
Background: Previous preterm birth and maternal age are known risk factors for preterm birth. Studies have shown a higher recurrence risk with a lower gestational age in the previous birth and that the clinical subtype of preterm birth is likely to recur. There is no current evidence regarding the risk of recurrent preterm birth in Iceland. This study aimed to investigate the risk of recurring preterm birth in Iceland from 1997 – 2018. Methods: A register-based cohort study was conducted using data from the Icelandic Medical Birth Register, identifying 23,096 women having their first two births in Iceland from 1997-2018. Odds ratios (ORs) and 95% confidence intervals (CIs) for the risk of a recurring preterm birth, overall and stratified by clinical subtype, gestational age, and maternal age, were estimated using logistic regression while adjusting for confounding variables. Results: A previous preterm birth increased the risk of a subsequent preterm birth significantly (aOR: 7.9), with a higher risk observed among women aged 35+ years. A recurring preterm birth was more likely to occur following a spontaneous preterm birth compared to a prior iatrogenic preterm birth (aOR: 8.85 vs. 5.58). Additionally, the likelihood of recurrence was higher among those with a history of preterm birth <32 weeks of gestation (aOR: 13.9). The gestational age and onset of previous preterm births were frequently repeated in subsequent preterm births. Conclusion: A previous preterm birth is a significant risk factor for recurrent preterm birth. Specifically, the association was stronger if the first preterm birth was spontaneous, occurred at <32 gestational weeks or maternal age was 35+ years at first birth. Bakgrunnur: Fyrri fyrirburafæðing og aldur móður eru þekktir áhættuþættir fyrirburafæðinga. Rannsóknir hafa sýnt að lægri meðgöngulengd og upphaf fæðingar eru líkleg til að endurtaka sig í næstu fæðingu. Ekkert hefur verið birt um endurteknar fyrirburafæðingar á Íslandi. Markmið rannsóknarinnar var að rannsaka áhættu á ...